Performance of Pulsator Clarifier (Low Turbidity) - K. AI-Dawery, Salam; M. Hussain, Raad; M. Shibeeb, Kadhem (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
Experimental and theoretical investigations are presented on flocculation process in pulsator clarifier. Experimental system was designed to study the factors that affecting the performance of pulsator clarifier. These factors were water level in vacuum chamber which range from 60 to 150 cm , rising time of water in vacuum chamber which having times of 20,30 & 40 seconds , and sludge blanket height which having heights of 20,30 & 40 cm .The turbidity and pH of raw water used were 200 NTU and 8.13 respectively. According to the jar test, the alum dose required for this turbidity was 20 mg/l .The performance parameters of pulsator clarifier such as , turbidity ,total solid TS , shear rate , volume concentration of sludge blanket and the flocculation criteria were studied. It was observed that by decreasing the water level in vacuum tube and by increasing the rising time and sludge blanket height , low turbidity of output water attained. Moreover, flocculation criteria value GCt was within the optimum range values (100-500) .A theoretical models was applied for total solids TS of output water .The difference between experimental and theoretical data was ranged between (11-24)% of mean deviation at water level range of (125-150)cm and sludge blanket height 20 cm.